Influences on teachers’ professional identity in schools in challenging circumstances: an empirical study of Chilean primary teachers’ perceptions - Lozano, Maria F. (2017)
There are so far few attempts to understand the teaching occupation and the meaning of being a good teacher as understood by teachers, a central issue in the improvement of schools. This study explores Chilean teachers’ perceptions of their professional identities, since conflict and stress around questions of identity affect teachers’ emotional well-being, impacting their capacity to engage emotionally with students and the wider school community, and thus their capacity to provide significant learning experiences which are key elements of successful learning. On the contrary, positive leadership and sufficient intellectual and material resources for reflection and discussion on the situation of conflicts on teachers’ professional identities can trigger processes of personal and professional growth, enhancing professional identity meanings, and thus effectiveness in providing significant learning experiences.